Legal interpretation from the perspective of French jurisprudence: from positivist exegesis to free scientific research - Sokalska, Edyta; Augustyniak, Małgorzata (Review of European and Comparative Law, 2022)
The “natural law” movement provoked some discussions on the method of interpretation of law within the European legal thought. Diverse methodological approaches referring to some social, historical, and multidimensional aspects and foundations of law were developed by French and German legal scholarship at the turn of the 19th and 20th centuries. The present article focuses on the main scientific positions on the method of interpretation of law present in French jurisprudence. Since the beginning of the 19th century, French legal studies were dominated by the positivist school of exegesis. Scholarship and legal practitioners sought the opportunity to rebuild their authority. It was accompanied by the attempts to prepare a new theoretical ground for the legal order. Then, some representatives of a new trend in scientific research considered pluralism of the methods applied in legal research. Raymond Saleilles postulated the need for the evolutionary perspective in legal science. This approach appears to be similar to the concept of the law of nature with variable content adopted by Rudolf Stammler in Germany. Since the last two decades of the 19th century, François Gény, the supporter of a greater flexibility in interpretation of a legal text, developed libre recherche scientifique. He questioned the idea of autonomy of the legal science, calling for its integration with other disciplines.